Enhanced Uniformity and Stability of Pb–Sn Perovskite Solar Cells via Me4NBr Passivation. Issue 14 (4th June 2019) - Du, Xingzhi; Qiu, Renzheng; Zou, Taoyu; Chen, Xuexian; Chen, Huanjun; Zhou, Hang
Abstract: Tin–lead (Sn–Pb) based hybrid perovskite solar cell is investigated as a potential solution to extend the light absorption spectrum range, and to reduce environmental hazard caused by lead in the perovskite materials. Nonetheless, due to the instability of tin, the Sn–Pb based perovskite solar cells suffer from more severe efficiency degradation when compared to the lead‐based perovskite solar cells, which restricts its further development. Here, a quaternary ammonium halide compound, Me4 NBr, is introduced to passivate the Sn–Pb based perovskite surface. The Me4 NBr effectively reduces the surface defects and enhances the open circuit voltage and fill factor of the Sn–Pb based perovskite solar cell. Moreover, the Me4 NBr treated Sn–Pb perovskite cells also demonstrate a significant stability enhancement when compared with the untreated Sn–Pb perovskite cells. Abstract : Me4 NBr is introduced to passivate the Sn–Pb based perovskite interface, leading to an improved efficiency of 13.97%, mainly due to the effective reduction of defects. By adopting the poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS)/poly(triarylamine) (PTAA) as the hole transport material (HTM), a Sn‐based perovskite solar cell with an efficiency of 14.56% is obtained. Furthermore, the Me4 NBr treated Sn–Pb perovskite cells also demonstrate a significant stability enhancement.